2002
DOI: 10.2136/sssaj2002.1788
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Sorption of Arsenate and Phosphate on Different Clay Minerals and Soils

Abstract: Sorption and desorption of AsO4 on or from different soil components may have a dominant role in regulating As mobility in soils. The objectives of this work were to provide information on the factors that influence the competitive sorption of AsO4 and PO4 in soil. We studied the competitive sorption of PO4 and AsO4 on selected phyllosilicates, metal oxides, synthetic organo‐mineral complexes, and soil samples as affected by pH (4.0–8.0), ligands concentration, surface coverage of the oxyanions on the samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
244
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(265 citation statements)
references
References 42 publications
20
244
0
1
Order By: Relevance
“…The ability of phosphate to compete with arsenate in binding at the surface sites of goethite as well as soil has well been documented [9][10][11][12][13]. In view of the fact that similar amounts of phosphate and arsenate were adsorbed on goethite samples at pH 3.0-8.5, Liu et al [12] speculated that these anions compete primarily for a similar set of surface sites on this mineral, while there are some sites that are specific for arsenate and phosphate adsorption, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of phosphate to compete with arsenate in binding at the surface sites of goethite as well as soil has well been documented [9][10][11][12][13]. In view of the fact that similar amounts of phosphate and arsenate were adsorbed on goethite samples at pH 3.0-8.5, Liu et al [12] speculated that these anions compete primarily for a similar set of surface sites on this mineral, while there are some sites that are specific for arsenate and phosphate adsorption, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate competes directly with both As(III) and As(V) for surface sites on Fe oxides (2,3,(5)(6)(7)(8)(9)(10), but has a stronger inhibitory effect on As(V) (see Part I,11). Inorganic carbon may also suppress As adsorption when concentrations are elevated in groundwater because of microbial respiration of organic carbon and/or carbonate mineral dissolution (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Manning and Goldberg (1997) found that Fe oxide was the most important mineral influencing adsorption of arsenate. In addition, organic matter, dissolved organic carbon and phosphate in soils have all been demonstrated to suppress arsenate adsorption by displacing adsorbed arsenate from soils (Grafe et al, 2001;Liu et al, 2001;Violante and Pigna, 2002). Some studies have also examined the influence of pH on arsenic adsorption by soils.…”
Section: Introductionmentioning
confidence: 99%